Laws Limiting Access to SNAP Benefits for People With Felony Drug Convictions: A Policy-Mapping Study. - Shah, Hridika; McCourt, Alexander D.; Bandara, Sachini (American Journal of Public Health, 2025)
Objectives. To map US state Supplemental Nutrition Assistance Program (SNAP) bans for individuals with felony drug convictions between 2004 and 2021. Methods. Using standard legal-mapping methodology, we categorized states as maintaining the lifetime ban imposed by federal law, modifying the lifetime ban, or fully opting out of the lifetime ban in each year. Among states with modified bans in 2021, we coded types of modifications. Results. As of 2021, 26 states and the District of Columbia fully opted out of the lifetime ban, 23 states modified bans, and 1 state maintained a lifetime ban. Among states with modified bans in 2021, 13 states required compliance with parole and probation, 12 states required drug treatment, 7 states required drug testing, and 9 states limited eligibility to certain populations. Conclusions. Most states effectively de-implemented the federal lifetime ban on SNAP for people with felony drug convictions by fully opting out or modifying bans over time. However, some states still had stringent modified ban provisions. Public Health Implications. These findings underscore the need to study the effects of this patchwork of drug conviction–related ban policies on substance use and nutrition-related outcomes. (Am J Public Health. 2025;115(2):170–177. https://doi.org/10.2105/AJPH.2024.307873)